Prevalence and risk factors of bovine mastitis from dairy farms in the north of Algeria - Dahmani, A; Zenia, S (Journal of the Hellenic Veterinary Medical Society, 2025)
A cross sectional study was conducted to determine the prevalence and risk factors of bovine mastitis from farms in three countries in the north of Algeria. 450 lactating cows were selected for the study. Cows with clinical mastitis (CM) were detected by clinical examination of the udder and determination of abnormalities in milk. California mastitis test (CMT) was used for screening subclinical mastitis (SCM). The results showed an overall 59.55% prevalence of mastitis. The subclinical mastitis (37.77%) is more prevalent than in the clinical type (21.77%). Risk factors analysis revealed significant association of mastitis between different groups. Cows in ages of 5–8 years (OR= 4.176 ; P<0.0001 ; 95% CI=2.594-6.724), having a parity of 3 to 5 years (OR = 3.549 ; P<0.0001 ; 95% CI = 2.217-5.680), Holstein breed (OR= 1.571 ; P= 0.049 ; 95% CI= 1.001-2.465), having a high milk production (OR= 1.808 ; P=0.015 95% CI=1.116-2.929), with cylindrical teat shape (OR= 5.191 ; P<0.0001 ; 95% CI=3.041-8.861), within the early-stage of lactation (OR= 6.095 ; <0.0001 ; 95% CI= 3.747-9.914) were significantly at risk of having CM. Also, intensive breeding (OR=8.53 ; 95% CI= 5.18-14.03), high condensation of animals (OR=2.77; 95%CI : 1.7-4.5), manure removal frequency more than a day (OR= 9.72; 95%CI= 5.843-16.175), presence of litter (OR=15.68 ;95% CI= 7.384-33.329), litter change frequency more than 3 days (OR=4.247 ; 95% CI= 2.44-7.378), control frequency of the milking machine more than a month (OR=2.21 ; 95% CI= 1.395-3.513), owner that do not take special clothing worn (OR=3.381 ; 95%CI= 1.81-6.31), absence of disinfection of the milking machine (OR=5.531; 95% CI= 3.076-9.945), owner that use the dishcloths for cleaning of teats (OR=1.813 ; 95%CI=1.114-2.95), the use of water and soap for cleaning the udder (OR=3.134 ; 95% CI=1.977-4.969), the staff that do not take attention to teat conformation and damage at milking (OR=2.416 , 95%CI= 1.42-4.107) were significantly associated with CM (P <0.0001). Bovine mastisis is prevalent in Algeria, and this is associated with both animal characteristics and environment factors. Better management practices in milking and adequate housing with proper sanitation should be provided.